2020
DOI: 10.1021/acs.orglett.0c02165
|View full text |Cite
|
Sign up to set email alerts
|

Dual Nickel-/Palladium-Catalyzed Reductive Cross-Coupling Reactions between Two Phenol Derivatives

Abstract: Cross-coupling between substrates that can be easily derived from phenols is highly attractive due to the abundance and low cost of phenols. Here, we report a dual nickel/palladium-catalyzed reductive cross-coupling between aryl tosylates and aryl triflates; both substrates can be accessed in just one step from readily available phenols. The reaction has a broad functional group tolerance and substrate scope (>60 examples). Furthermore, it displays low sensitivity to steric effects demonstrated by the synthesi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Transition metal-catalyzed C­(sp 2 )–C­(sp 2 ) reductive cross-coupling reactions of two aryl electrophiles have received a great deal of attention as some of the most efficient methods for the synthesis of biaryls due to the wide availability of electrophiles and because the reactions circumvent the tedious preparation of organometallic reagents . To date, various aryl halides and O-based aryl electrophiles have been utilized in such transformations. In recent years, sporadic examples of C­(Ar 1 )–C­(Ar 2 ) reductive cross-coupling involving aryl amine derivatives, , pyridyl sulfone, and aryl nitriles have also been reported.…”
mentioning
confidence: 99%
“…Transition metal-catalyzed C­(sp 2 )–C­(sp 2 ) reductive cross-coupling reactions of two aryl electrophiles have received a great deal of attention as some of the most efficient methods for the synthesis of biaryls due to the wide availability of electrophiles and because the reactions circumvent the tedious preparation of organometallic reagents . To date, various aryl halides and O-based aryl electrophiles have been utilized in such transformations. In recent years, sporadic examples of C­(Ar 1 )–C­(Ar 2 ) reductive cross-coupling involving aryl amine derivatives, , pyridyl sulfone, and aryl nitriles have also been reported.…”
mentioning
confidence: 99%
“…This strategy relied on the selective oxidative addition of two catalysts into each of the aryl electrophiles; the nickel catalyst favored oxidative addition into the C–Br bond, while the palladium catalyst favored oxidative addition into the C–OTf bond. The use of multimetallic catalyst systems have since been developed to address challenges associated with C­(sp 2 )–C­(sp 2 ) cross-coupling …”
mentioning
confidence: 99%
“…Also in 2020, Zhong et al reported another dual nickel-/palladium-catalyzed reductive cross-coupling between aryl tosylates 253 and aryl triflates 254, both of which could be easily accessed from readily available phenols 252. 70 By combining different ligands, Pd/L1 selectively activates the tosylate C-O bond, while Ni/L2 prefers to activate the triflate, leading overall to the formation of crosscoupling products 255 (Scheme 49).…”
Section: Or Rmentioning
confidence: 99%